(untitled) (Research, Society and Development, 2022)
Objective: To observe whether there is agreement between the examiners in the interpretation of periapical radiographs of endodontic treatment control, seeking to evaluate the limit of root canal filling. Methodology: For this, 20 periapical radiographs were used, of which 10 radiographs corresponded to the immediate postoperative period and 10 control radiographs, from 10 completed endodontic treatments, performed at the Faculty of Dentistry of Pernambuco. Three professors from the Specialization Course in Endodontics of the same teaching institution were asked to evaluate the radiographs of the 10 endodontic treatments and to answer a questionnaire regarding the referred cases. The radiographic analysis of root canal fillings was performed under appropriate conditions for proper interpretation. Results: Regarding the inter-examiner agreement, it was found that, in relation to the periapical condition, examiners 1 and 2 presented a coincidence in 50% of the cases, examiners 1 and 3, in 60% and examiners 2 and 3, by 70%. Regarding the agreement regarding the root canal filling limit, it was observed that examiners 1 and 2 agreed in 100% of the cases and examiners 1 and 3, and 2 and 3, in 90% of the cases. Providing an average inter-examiner agreement of 60% in the first evaluation and 93.33% in the second evaluation. Final considerations: Based on the results obtained, it is concluded that there was a high agreement between the examiners, mainly due to the vast experience of the professionals.